2018
DOI: 10.2147/ndt.s154809
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-alpha antibody attenuates subarachnoid hemorrhage-induced apoptosis in the hypothalamus by inhibiting the activation of Erk

Abstract: BackgroundSubarachnoid hemorrhage (SAH) can induce apoptosis in many regions of the brain including the cortex and hippocampus. However, few studies have focused on apoptosis in the hypothalamus after SAH. Although some antiapoptotic strategies have been developed for SAH, such as anti-tumor necrosis factor-alpha (TNF-α) antibody, the molecular mechanisms underlying this condition have yet to be elucidated. Therefore, the purpose of this study was to evaluate whether SAH could induce apoptosis in the hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A variety of TNF-α inhibitors have been approved for the treatment of SAH-induced apoptosis. They include anti-tumor necrosis factor-alpha antibody [40], acetylcholine [39], and ethyl pyruvate [41]. We found the treatment with RTA 408 reversed the increased expression of cleaved caspase-3 and TNF-α in the denate gyrus after SAH.…”
Section: Plos Onementioning
confidence: 76%
See 1 more Smart Citation
“…A variety of TNF-α inhibitors have been approved for the treatment of SAH-induced apoptosis. They include anti-tumor necrosis factor-alpha antibody [40], acetylcholine [39], and ethyl pyruvate [41]. We found the treatment with RTA 408 reversed the increased expression of cleaved caspase-3 and TNF-α in the denate gyrus after SAH.…”
Section: Plos Onementioning
confidence: 76%
“…TNF-α is a pro-inflammatory cytokine involved in neuronal inflammation, apoptosis, and necrosis [39]. TNF-α has been found to be upregulated in both the cerebral cortex and hippocampus in an SAH animal model, and it may be responsible for SAH-induced apoptosis [39][40][41]. A variety of TNF-α inhibitors have been approved for the treatment of SAH-induced apoptosis.…”
Section: Plos Onementioning
confidence: 99%
“…The cerebrospinal uid of SAH patients shows increased TNF levels in platelets and microvessel endothelial cells, suggesting that cerebral vasospasm triggers in ammatory processes that may contribute to brain injury (Eisenhut 2014). SAH-induced neuronal apoptosis can also be alleviated by protecting the BBB (Liu et al 2013) and by delivering anti-TNF-a antibody to the hypothalamus (Ma et al 2018). And hypothalamic in ammation after stroke has been linked to the activity of neuronal POMC and NPY (Pascoal et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of mAbs is an effective and specific technique to block signaling pathways activated by a pro-inflammatory cytokine. Previous work has also demonstrated that anti-cytokine therapeutic strategies attenuate the effects of traumatic brain injury [ 88 ], stroke [ 54 ], and subarachnoid hemorrhage [ 89 ] in adult rodents.…”
Section: Anti-cytokines Antibodies As a Potential Neuroprotective mentioning
confidence: 99%
“…The mAbs were administered as systemic intravenous infusions because this is a clinically relevant route of administration and directly exposes the fetus to the mAb over an extended interval of time. Other routes of administration have previously been used to deliver antibodies directly into the brain via intracerebral injections in experimental studies of adult rodents [ 89 , 93 ]. Intracerebral injections of drugs facilitate the direct entry of drugs into the brain by circumventing the BBB.…”
Section: Anti-cytokines Antibodies As a Potential Neuroprotective mentioning
confidence: 99%